Analisis Perbandingan Kualitas Pelayanan Terminal Penumpang di Pelabuhan Tanjung Priok dan Pelabuhan Surabaya - Leonardus Panggih Yudanto; Nova Triningsih; Amanda Hidayat; Narul Fadzry; Siti Sahara (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze the comparison of service quality of passenger terminals at the Port of Tanjung Priok and the Port of Surabaya. The method used is a survey using a questionnaire to respondents who have used the two passenger terminals. The collected data were analyzed using descriptive analysis techniques and independent sample t-test. The results showed that in general the service quality of the passenger terminals at Tanjung Priok Port and Surabaya Port was considered quite good by the respondents. However, there are significant differences in several aspects of service quality between the two terminals. The passenger terminal at the Port of Surabaya is considered better in terms of security and safety, comfort, as well as facilities and services. Meanwhile, the passenger terminal at Tanjung Priok Port is considered better in terms of waiting time and queue time